La “descrizione dei tempi” all’alba dell’espansione islamica : Un’indagine sulla storiografia greca, siriaca e araba fra VII e VIII secolo - Conterno, Maria (2014)
The 7-8th centuries are commonly believed tohave beena stagnant phase of Byzantine historiography. This book investigates the writing of history in Greek and Syriacduring this period through the study of four later chronicles which used lost 7-8th-century sources. The materials shared by these texts shed light on the sources themselves and on the practice of "memory keeping" among Christians in such a crucial age.